BOOK REVIEWS (Journal of Finance, 1971)
Book reviewed in this article: Industry Production Behavior: The Order‐Stock Distinction . By D avid A. B elsley . Mathematical Theories of Economic Growth . By E dwin B urmeister and A. R odney D obell . America's Greatest Depression, 1929–1941 . By L ester V. C handler . Modern Political Arithmetic . By B ruce F. D avie and B ruce F. D uncombe . The Seasonal Variation of Interest Rates . By S tanley D iller . Monetary Statistics of the United States: Estimates, Sources, Methods . By M ilton F riedman and A nna jacobson S chwartz . International Comparisons of Money Velocity and Wage Mark‐ups . By J ohn H. H otson . Economics: Mainstream Readings and Radical Critiques . Edited with Introductions by D avid M ermelstein . Managing the Resource Allocation Process: A Study of Corporate Planning and Investment . By J oseph L. B ower . Principles of Financial Management . By W ard S. C urran . Basic Managerial Finance . By A dolph E. G runewald and E rwin E sser N emmers . The Investment Process. Edited by J ohn M. L ishan and D avid T. C rary . L'Ordinateur Speculateur . By J ean S emah , C hristian S erres and B ernard T essier . The Formulation of Expected Interest Rates: An Examination of Alternative Hypotheses . By F rank J. B onello . Economic Policy and the Regulation of Corporate Securities . Edited by H enry G. M anne . Money and Banking: Theory, Analysis, and Policy . Edited by S. M ittra . A Financial History of the United States . By M argaret G. M yers . Money in an African Context By W. T. N ewlyn . Financial Institutions and Markets By M urray E. P olakoff and others. Finance and Development in Thailand . By A lek A. R ozental . Bank Costs for Decision Making: Costing Procedures for Pricing Bank Services . By J ohn R. W alker . Approaches to Greater Flexibility of Exchange Rates: The Bürgenstock Papers . Arranged by C. F red B ergston , G eorge N. H alm , F ritz M achlup , and R obert V. R oosa . The International, Adjustment Mechanism . C aves , et al . Balance‐of‐Payments Policy . By B. J. C ohen . The International Monetary System . By H erbert G. G rubel . Baltimore: Penguin Books Inc., 1970. Pp. 208. $1.65 (paper). International Economics . By R obert A. M undell . Federal Revenue Sharing With the States . By M ichael E. L evy and J uan de T orres . The Politics and Economics of State‐Local Finance . By L. L. E cker ‐R acz .